DISTRIBUTION PATTERNS, GROWTH AND BIOMASS ALLOCATION OF CRYPTOCORYNE CILIATA (ROXBURGH) SCHOTT (ARACEAE) FROM SUNGAI SARAWAK, KUCHING, SARAWAK, MALAYSIA - A Simon; Ipor I B; Tawan C S (Tropical Life Sciences Research, 2008)
The distribution pattern of Cryptocoryne ciliata (Roxburgh) Schott (Araceae) along 22 km of Sungai Sarawak, Kuching was studied. There was a morphological variation between the plants collected at different sampling points. Number of plants, leaves per quadrate, total plant dry weight, leaf area, dry weight for leaves, rhizomes, roots, runners and syncarpous fruit were recorded. Specific leaf area (SLA), leaf area ratio (LAR), leaf weight ratio (LWR), rhizome weight ratio (RhWR), root weight ratio (RWR), shoot weight ratio (SWR), and runner weight ratio (RuWR) were also recorded. Soil analyses and the in situ water measurement were also carried out. Growth analyses with regards to shading and photosynthetic rates were also investigated. Corak sebaran Cryptocoryne ciliata (Roxburgh) Schott (Araceae) sepanjang 22 km di Sungai Sarawak, Kuching telah dikaji. Terdapat perbezaan morfologi antara tumbuhan yang disampel daripada lokasi yang berbeza. Jumlah bilangan tumbuhan, jumlah daun per kuadrat, jumlah berat kering tumbuhan, luas permukaan daun, berat kering daun, rizom, akar, runners dan buah sinkarp direkodkan. Luas daun spesifik (SLA), nisbah luas daun (LAR), nisbah berat daun (LWR), nisbah berat rizom (RhWR), nisbah berat akar (RWR) nisbah berat pucuk (SWR) dan nisbah berat runner (RUWR) turut direkod. Analisa tanah dan sukatan air in situ turut dijalankan. Analisa pertumbuhan pokok berkait dengan lindungan dan kadar fotosintetik turut dikaji.